P820 The interleukin-6 receptor as a target for prevention of Crohn's disease and ulcerative colitis; a Mendelian randomisation study. (16th January 2018) - Parisinos, C A; Serghiou, S; Katsoulis, M; Patel, R S; Hemingway, H; Hingorani, A D
Abstract: Background: Interleukin-6 signalling is likely to contribute to the pathogenesis of inflammatory bowel disease (IBD). 1 Blockade of the interleukin-6 receptor (IL6R) with a monoclonal antibody (tocilizumab) is licensed for treatment of rheumatoid arthritis. 2 Clinical trials of IL6R inhibitors in IBD have had varying efficacy. 3 Whether IL6R blockade reduces the risk of developing IBD in the population is unknown. Mendelian randomisation (MR) is a genetic epidemiological approach that can utilise genetic variant properties (random allocation at conception, free from confounding and reverse causation (the genome is non-modifiable)) to validate drug targets of interest; causal inferences from MR are analogous to those of randomised controlled trials (RCTs). Similar to tocilizumab, the IL6R SNP rs2228145 associates with impaired IL6R signalling and downstream effects (higher soluble IL6R (s-IL6R) levels, lower CRP and fibrinogen levels), making it an attractive genetic instrument for drug target validation. 4 Methods: We performed a two sample MR using rs2228145 to evaluate the role of IL6R inhibition for primary prevention of IBD. Genes-IL6R associations were estimated in 1650 individuals, as a proxy for defective IL6R signalling. 5 Gene–IBD associations were estimated in 49833 cases and 61630 ancestry matched controls from publically available GWAS data. 6, 7 The Wald ratio was used to estimate odds ratios (OR) for incident disease. Results: In a meta-analysis of 26788 cases with Crohn's disease (CD), 23045 with ulcerative colitis (UC)) and 61630 controls, genetically elevated s-IL6R decreased odds of CD (odds ratio (OR) 0.87, 95% CI 0.82–0.92, p = 0.00001463) and UC (OR 0.92, 95% CI 0.89–0.99, p = 0.0378) per 2-fold increment. Conclusions: On the basis of genetic evidence in human beings, IL6R signalling seems to have a causal role in the development of CD and UC. IL6R blockade is a novel therapeutic target for primary prevention of IBD, should future risk scores allow accurate stratification. Genetic studies in IBD could be used more widely to validate and prioritise novel drug targets or to repurpose existing agents for new therapeutic uses. References: 1. Hunter CA, Jones SA. IL-6 as a keystone cytokine in health and disease. Nat Immunol, 2015. 2. Neurath MF, Current and emerging therapeutic targets for IBD. Nat Rev Gastroenterol Hepatol, 2017. 3. Coskun M, Vermeire S, Nielsen OH. Novel targeted therapies for inflammatory bowel disease, Trends Pharmacol Sci, 2017. 4. Interleukin-6 Receptor Mendelian Randomisation Analysis (IL6R MR) Consortium, Swerdlow DI, Holmes M V, et al . The interleukin-6 receptor as a target for prevention of coronary heart disease: a mendelian randomisation analysis. Lancet, 2012. 5. IL6R Genetics Consortium Emerging Risk Factors Collaboration, Sarwar N, Butterworth AS, et al . Interleukin-6 receptor pathways in coronary heart disease: a collaborative meta-analysis of 82 studies. Lancet, 2012. 6. Liu JZ, van Sommeren S, Huang H, et al . Association analyses identify 38 susceptibility loci for inflammatory bowel disease and highlight shared genetic risk across populations. Nat Genet, 2015. 7. de Lange KM, Moutsianas L, Lee JC, et al. Genome-wide association study implicates immune activation of multiple integrin genes in inflammatory bowel disease. Nat Genet, 2017.